2020
DOI: 10.3389/fcell.2020.602956
|View full text |Cite
|
Sign up to set email alerts
|

ATR Kinase Is a Crucial Player Mediating the DNA Damage Response in Trypanosoma brucei

Abstract: DNA double-strand breaks (DSBs) are among the most deleterious lesions that threaten genome integrity. To address DSBs, eukaryotic cells of model organisms have evolved a complex network of cellular pathways that are able to detect DNA damage, activate a checkpoint response to delay cell cycle progression, recruit the proper repair machinery, and resume the cell cycle once the DNA damage is repaired. Cell cycle checkpoints are primarily regulated by the apical kinases ATR and ATM, which are conserved throughou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Consistent with TbATR having wide roles in T. brucei biology - akin to the emerging data on diverse ATR functions in other eukaryotes - analysis of various cellular phenotypes reveals more pleotrophic effects after its loss than the impaired cell cycle progression, increased DNA damage and altered VSG expression control documented previously 34,35,37 . First, TbATR depleted cells display numerous changes in their nuclear ultrastructure.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Consistent with TbATR having wide roles in T. brucei biology - akin to the emerging data on diverse ATR functions in other eukaryotes - analysis of various cellular phenotypes reveals more pleotrophic effects after its loss than the impaired cell cycle progression, increased DNA damage and altered VSG expression control documented previously 34,35,37 . First, TbATR depleted cells display numerous changes in their nuclear ultrastructure.…”
Section: Discussionsupporting
confidence: 60%
“…More recently, wider roles for ATR have been recognised, including maintaining the integrity of the nuclear envelope 27,29,30 , nucleolus 28 and centrosome 31 . In the kinetoplastid parasite T. brucei , TbATR acts in cell cycle progression and DNA double-strand break repair 37 , and in mammal-infective BSF cells the kinase acts in monoallelic VSG expression and VSG recombination during host immune evasion by antigenic variation 34 . However, whether such VSG-related functions could explain why loss of TbATR is essential in mammal-infective T. brucei , but not in tsetse-infective cells, is questionable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, what aspect of ATR function results in T. brucei death after the loss of the PK is unknown. In this regard, recent work in insect stage T. brucei revealed that depletion of ATR only moderately affects parasite proliferation and cell cycle progression, despite playing an important role during HR and damage signaling in this life cycle stage in response to ionizing radiation (IR) (Marin et al, 2020). This dichotomy likely reflects alternative demands on repair and replication in distinct life cycle stages.…”
Section: The Atr Kinasementioning
confidence: 99%